Self-regulation and Chinese character learning strategies in Irish Higher Education - JIANG, NING (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2019)
Chinese language studies have been recently growing in English-speaking nations at a rapid speed, indicating the possible emergence of a boom period of Chinese language learning around the globe. However, despite this surge of Chinese language education, Chinese is still described as one of the most difficult languages to acquire. In the research field of Chinese language learning as a foreign language, few studies have investigated how learners overcome the barriers to acquiring this difficult language and its unfamiliar writing system. Therefore, there remains a severe lack of research on this aspect, especially with regard to Irish students. This study was conducted to explore alphabet-based learners language learning strategies and self-regulatory learning in the context of Irish higher education with a mixed methods approach, combining a longitudinal case study of 8 participants over one academic year and a national survey of 115 Chinese language learners in all Irish Higher Education institutions which teach Chinese. By doing so, this study explored alphabet-based learners language learning strategies and self-regulatory learning in the context of Irish higher education, among students engaged in the process of Chinese characters acquisition. Furthermore, this study discussed which strategies positively affect students language learning outcomes in terms of their Chinese character acquisition. Finally, other factors that may affect learners strategy use to learn Chinese characters and control self-regulation were also discussed in the case study. As a result, this study firstly approaches the issue of language learning strategies and self-regulatory learning during Chinese character acquisition in Irish higher education. In addition, this study makes a significant contribution to theory-building in the area of language learning strategies through an application of new concepts to the, as yet, unexplored area of the learning of character-based Chinese writing systems by students from an alphabetic writing system background. In addition, this study explores the application of a mixed research methods in the field of Chinese character acquisition and provides a structured research design for future studies.
APPROVED
Keywords: Chinese character learning; Learning strategies; Self-regulation; Language learning